Aššur is king! Aššur is king!: religion in the exercise of power in the Neo-Assyrian Empire - Holloway, Steven W. (Culture and history of the ancient Near East 1566-2055, 2002)
Neo-Assyrian religious imperialism was expressed by punitive measures such as "godnapping", and by the geographical focus and extent of the material support the Assyrians lavished on favoured polities. This work is devoted to Neo-Assyrian religious imperialism